Exploring Cyber Secure and Resilient Approaches with Feature‐Based Product Line Engineering. Issue 3 (8th October 2020) - Young, Bobbi; Wilson, Beth
ABSTRACT: The INCOSE Systems Security Engineering Working Group and Product Line Engineering Working Group completed a joint project exploring cyber secure and resilient approaches with feature‐based product line engineering. The project output results are in this INCOSE INSIGHT theme issue (Volume 23, Issue 3). This article introduces the theme issue and the articles exploring the intersection between systems security engineering and product line engineering. The focus includes techniques for implementing systems security as part of a product line design, patterns for product line architectures addressing systems security, and variation management approaches for security and resilient product line products.